Thermal-hydraulic characteristics and performance of 3D straight channel based printed circuit heat exchanger. (5th April 2016) - Aneesh, A.M.; Sharma, Atul; Srivastava, Atul; Vyas, K.N.; Chaudhuri, Paritosh
Highlights: The effect of operating conditions is studied. Thermal-hydraulic characteristics are analyzed by various types of flow patterns. Thermal hydraulic performance is better for single as compared to double banking. Performance is the same for aligned and staggered arrangement of channels. Heat transfer increases asymptotically with increasing number of dimples. Abstract: CFD study is done to propose an efficient PCHE (Printed Circuit Heat Exchanger) model; used as a recuperator in International Thermonuclear Experimental Reactor (ITER). 3D steady-state conjugate heat-transfer simulations are done with helium as a working fluid and alloy 617 as the solid substrate. Effect of variation of thermo-physical properties, operating conditions and three different design modifications are studied. Thermal hydraulic performance is found better for single as compared to double banking and is the same for aligned as compared to the staggered arrangement of the hot and cold channels. PCHE models with hemispherical dimples are found to give better thermal hydraulic performance. The performance is presented for the variation of the heat transfer density (for a PCHE model) and the pressure drop (in the hot and cold channel). Various types of flow patterns are presented to analyze the thermal-hydraulic characteristics − leading to the heat transfer enhancement by the dimples.